Chronic axillary sinus in a child - Raju, Cholaraju Siva Ranadheer; Gajanthody, Suhitha; Ahamed, Ashraf; Ali, Ameer (Indian Journal of Child Health, 2019)
Chronic discharging sinus in the axilla is of very rare occurrence in pediatric age. Such a presentation, especially with a previous history of trauma, should be viewed with caution. Various possibilities including tuberculosis are considered. Appropriate investigations and thorough wound management will help in the prevention of long-term morbidity. We report a case of the chronic discharging axillary sinus in a child and review literature.